FROM FANDOM CONFLICT TO “SEABLINGS”: THE CONSTRUCTION OF A DIGITAL SOUTHEAST ASIAN IDENTITY IN RESPONSE TO TRANSNATIONAL RACISM - Early Nalvi Hoata Sahureka; Luthfia Khairunnisa; Nazilla Putri Priantika; Malika Zahwa Sabrina Gusfayani; Siti Fatimah; Thyta Meytafi (Verity: Jurnal Ilmiah Hubungan Internasional (International Relations Journal), 2026)
This article analyzes how SEAblings was constructed as a Southeast Asian digital identity through social media interactions in response to transnational racist discourse. The phenomenon emerged from an online dispute following DAY6’s concert in Kuala Lumpur on 31 January 2026, which later developed into a wider digital controversy involving racialized insults against Southeast Asian fans and communities. Drawing on constructivist International Relations, this article conceptualizes identity as a social construction formed through shared meanings, interaction, and representation. This study uses a qualitative descriptive design based on literature review and document analysis. The data consist of academic literature, online news reports, social media monitoring reports, and publicly available digital traces documenting the SEAblings controversy. The analysis is guided by four indicators: boundary-making, shared symbols, affective solidarity, and narrative reversal. The findings show that SEAblings emerged when Southeast Asian users collectively drew symbolic boundaries between “us” and “them,” circulated hashtags, memes, and regional expressions as shared symbols, transformed anger and humor into affective solidarity, and transformed negative narratives about Southeast Asia into expressions of regional pride. The article argues that SEAblings represents a citizen-led and situational form of Southeast Asian digital identity. It contributes to International Relations by showing that regional identity is not produced only through states, diplomacy, or formal institutions, but can also emerge from everyday digital practices, symbolic struggles, and affective interactions among ordinary social media users.